Fiscal Decentralization and Disparity of Access to Primary Education in Indonesia - Doriza, Shinta; Purwanto, Deniey Adi; Maulida, Ernita (Universitas Muhammdaiyah Surakarta, 2013)
In education, one crusial issue of development is the disparity of primary education access. Using 440 regions database from 2005-2009, this study is aim to analize the impact of fiscal decentralization in reducing the enrolement of primary education in Indonesia. Three factors were included, i.e fiscal decentralization, socioeconomic factors and regional characteristics. The result of panel data estimation using fixed-effect approach on this study is that DAK for Education, DAK Non Education, and PAD have significant impact in reducing education acess disparity along with poverty and regional characteristic such as Java-non Java regions. For education level, another variable was also found significant including education of the society and regional characteristic such as proliferated-non proliferated regions. In general there is a facts and proves that fiscal decentralization improve education access equality, but several effort need to done to optimalize the equalization of primary education access in Indonesia.